Electrochemical removal of Pb2+ using Fe3O4-doped modified electrode - ZHANG Yihao; HOU Baolin; WANG Jiaxin; ZHANG Ting; REN Zhiwen (Gongye shui chuli)
For efficient electrochemical removal of Pb2+ from water bodies, Fe3O4 doped modified electrodes were prepared by loading a mixture of Fe3O4, powdered activated carbon, acetylene black and polyvinyl alcohol onto graphite paper with the coating method. The electrochemical removal of Pb2+ with Fe3O4-doped modified electrode was carried out in a differential column batch reactor mode, and the effects of voltage, temperature, operation time,concentration, and other factors on the Pb2+ removal performance were investigated. The reusability and stability of the electrode were evaluated based on cycle trials. The results showed that the prepared electrodes had abundant surface pores and uniform pore size. The removal of Pb2+ by the electrochemical system reached 98.73% after 150 min at a voltage of 1.4 V, and the extension of the operation time could significantly strengthen the removal of Pb2+. In the temperature range of 10-35 ℃, the increase of temperature was favorable for the electrochemical removal of Pb2+. The electrochemical system had good applicability and adaptability at different Pb2+ concentrations. With the increase of the initial Pb2+ concentration, the energy consumption for treating unit volume of Pb2+ wastewater increased gradually, but the energy consumption for removing unit mass of Pb2+ decreased on the contrary, The fitting results showed that the removal process of Pb2+ was in accordance with the pseudo-first order kinetics. The electrochemical system still maintained the original removal effect after eight cycles, presenting commendable reusability and stability.